Leukemia Morbidity and Mortality among Children Admitted to Hiwa Hospital from January 2015 to January 2022: A Retrospective Study - Azize, Pary Mohammad (Sulaimani Journal for Pure and Applied Sciences, 2023)
In 2016, 1 out of 3 cancer patients aged less than 20 years old were diagnosed with leukemia. Globally, leukemia is the most common malignancy in children and teenagers. This study aimed to determine leukemia cases' morbidity and mortality rates and their distribution in different areas of Sulaimani, Iraq, for seven years. This retrospective study is based on the Hospital Information System children's leukemia data from January 2015 to January 2022 at the Hematology Department, Hiwa Oncology/Hematology Hospital, Sulaimani, Iraq, using a Cox regression model (Cox, 1972). In 616 recorded children leukemia cases during seven years, 549(89.1%) of them were alive, and only 67(10.9%) died. The majority were male, aged between 5-10 years. Nearly 222(36%) of the patients had A+ blood group, followed by 210(34.1%) O+ blood group, while the minority was ABgroup. The study result shows that age, and blood group, were risk factors for increasing leukemia chances by Exp (-0.074) =0.929. Leukemia morbidity rises significantly with age, and leukemia's morbidity rate increases gradually with time. While mortality was decreased.Depends on the forecastingfor the next 10 years. Both ALL and AML were common malignancies among diagnosed children.
Keywords: Leukemia; risk factors; age; gender; morbidity; mortality